Using ECL Media to Improve Information Literacy of Islamic Elementary School Students - Naila, Ishmatun; Ridlwan, Muhammad; Nurdianah, Lutfiyan (Mimbar Sekolah Dasar, 2022)
This research examines the use of ECL media to improve literacy information of Islamic elementary school students. The method used was repeated pre-experiment without a control class. The research design used was one group pre-test and post-test. Data were analyzed using paired t-test, n-gain calculation, and ANOVA using IBM SPSS Version 25. The results showed an increase in students' information literacy, which was statistically significant at 5% alpha after learning using ECL media. The mean n-gain for the three classes was in the medium category and does not differ in three experimental classes, and more than 90% students responded positively to the teaching using ECL media. Based on the results, ECL media effectively improved students' information literacy. This research will be a new reference to improve the information literacy of elementary school students, especially first graders, for teachers, parents, and students independently.